(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Among the categories of personal data, a special status is recognized to genetic information, as genetic identity is a relational identity; personal genetic information is structurally shared with other subjects belonging to the same "biological group" and moreover in this kind of information knowledge and prediction of the risk of getting sick are intertwined. For this reason, biological samples, and the genetic personal data connected to them, are subject to special protection which makes the question of regulating their acquisition, storage, use, distribution and sharing specifically complex. Focusing on this issue of great general bioethical importance, particularly in the current context of the Covid-19 pandemic, the article highlights some theoretical-philosophical problems which underlie, from the very beginning, the bioethical and bio-juridical debate regarding both the status of biological samples donated for genetic research purposes, and the right of sample donors to choose whether or not to know individual results of potential clinical relevance; these issues are explored with special reference to genetic research with minors.